Antioxidant activity of probiotic lactic acid bacteria isolated from Mongolian airag - Uugantsetseg, E; Batjargal, B (Mongolian Journal of Chemistry, 2014)
This research aimed to determine the antioxidant activity of probiotic lactic acid bacteria isolated from airag. In this study, 42 lactic acid bacteria were isolated from Mongolian airag. All isolates were identified by using morphological, biochemical and physiological methods. The isolated bacteria were studied for antagonistic effects on Enterococcus faecalis, Escherichia coli, Pseudomonas aeruginosa and Staphylococcus aureus, 22 strains showed antibacterial activity. When we examined their probiotic properties such as bile acid tolerance and gastric acid tolerance, it is shown that only 6 bacterial strains can survive up to 3 hours in a pH 3.0 acid environment and up to 8 hours in 0.3% bile acid environment. Selected probiotic strains were further identified to species by API 50CHL system. Antioxidant activity of probiotic strains were determined by 1,1-diphenyl-2 picrylhydrazyl (DPPH) assay. While the antioxidant activity in cell free supernatant fluctuated between the range of 26.1-38.4%, the antioxidant activity after 72 hours of fermentation in the whey fraction was between 17.23-55.12%. DOI: http://doi.dx.org/10.5564/mjc.v15i0.327 Mongolian Journal of Chemistry 15 (41), 2014, p73-78